Writing the self : the life and philosophy of a dissenting Bengali Baul Guru - Openshaw, Jeanne (New Delhi : Oxford University Press, 2010)
Includes transliteration in Bengali of Raj Khyapa's autobiography.
Includes bibliographical references (p. [247]-260) and index.
Includes text in Bengali
Keywords: KHYAPA, RAJ,A -- 1869-1946.; BAULS -- INDIA -- BENGAL; BENGAL (INDIA) -- COLONIAL INFLUENCE